Hak Asasi Manusia (HAM) Perspektif Al-Qur’an (Analisis Maqâshid Asy-Syarî’ah Dengan Pendekatan Tafsir) - Jufri Hasani Z (Istinarah: Riset Keagamaan, Sosial dan Budaya, 2021)
Humans as noble creatures have rights that must be given by various parties. Oppression, colonization and slavery and discrimination are forms of action that do not respect human rights. The sentence "Colonialism over the world must be abolished" contained in the preamble of the 1945 Constitution emphasizes how human dignity and freedom must not be taken away. This paper tries to reveal Human Rights (HAM) from the perspective of the Qur'an by using the maqâshid as-syarî'ah concept as the scalpel. Discussions about human rights in the world have emerged since the 18th century ago, while the formulation of human rights that are considered legal and standardized today is that published by the United Nations Agency, which was declared on December 10, 1948 and later. known as "The Universal Declaration of Human Rights". The struggle for human rights is increasing considering the condition of human rights violations that occur in many parts of the world. In Islam, through the signs of the Qur'an, general rules related to human rights are found, including: 1) the right to life; 2) the right to education; 3) the right to freedom and protection of property; 4) the right to honor and; 5) religious rights. This research is in the form of library research using thematic interpretation methods based on themes using the maqâshid ash-syarî'ah approach.